Selected Transition and Mediterranean Countries : An Institutional Primer on EMU and EU Relations - Feldman, Robert (IMF Working Papers; Working Paper ;, 1998)
Economic and Monetary Union (EMU) has a number of institutional implications for the transition countries of Central and Eastern Europe and selected Mediterranean countries that aspire to join the European Union (EU). After describing the current institutional framework for their relations with the EU, the paper examines two basic categories of institutional effects: those stemming from the need to satisfy the Maastricht convergence criteria before joining the euro area, and those stemming from the need to adopt the EU's institutional and legal provisions in the area of EMU.